2020
DOI: 10.1002/aoc.5726
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanism and Kinetics study on Addition of CCl4 to 1‐hexene Catalyzed by Mo‐Mo Quintuply‐bond

Abstract: Transition metal-catalyzed atom transfer radical addition (ATRA) reactions are an effective and versatile strategy for constructing carbon-carbon bonds in organic synthesis. Typically, the metal center in this metal-assisted radical transformation undergoes a reversible redox process. In this work, a quintuply-bonded dinuclear complex, Mo 2 (N^N) 2 {N^N = μ-κ 2-CH[N(2,6-iPr 2 C 6 H 3)] 2 }, has been investigated as potential catalyst for radical addition of CCl 4 to 1-hexene by performing density functional th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
3
1
Order By: Relevance
“…Our calculated ΔG # is slightly smaller than that determined by kinetic experimental results, 26.0kcal/mol at 303K [24]. The experimental value is larger because it is determined in the presence of excess CCl 4 and pyridine; the coordination of pyridine suppresses the reaction, which has been found in former studies [2,8]. CCl 3 addition to 1-hexene: The dissociated •CCl 3 radical attacks the C1 atom of 1-hexene with a energy barrier of 9.0 kcal/mol (Fig.…”
Section: Computational Detailscontrasting
confidence: 47%
See 2 more Smart Citations
“…Our calculated ΔG # is slightly smaller than that determined by kinetic experimental results, 26.0kcal/mol at 303K [24]. The experimental value is larger because it is determined in the presence of excess CCl 4 and pyridine; the coordination of pyridine suppresses the reaction, which has been found in former studies [2,8]. CCl 3 addition to 1-hexene: The dissociated •CCl 3 radical attacks the C1 atom of 1-hexene with a energy barrier of 9.0 kcal/mol (Fig.…”
Section: Computational Detailscontrasting
confidence: 47%
“…In this reaction process, the spin electron density migrates from the C atom of CCl 3 radical to the C1 atom of 1-hexene, COM7 forms. This step has been discussed in our former work [8]. Then the calculated Gibbs free energies were converted to absolute electron redox potential according to Nernst equation:…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mashima and co‐workers demonstrated that this reactivity allows for catalytic hydrodehalogenation, addition and polymerization reactions [59] . Experimental as well as quantum chemical studies [60] show that the quadruple bond undergoes one‐electron reductive abstraction of the halide allowing for subsequent radical pathways.…”
Section: Cooperative Effects In Homo‐multimetallic Complexes With Short Metal‐metal Distancesmentioning
confidence: 99%